Q-switched ytterbium-doped fiber laser with zinc oxide based saturable absorber - Ahmad, Harith; Salim, M.A.M.; Ismail, Mohammad Faizal; Harun, Sulaiman Wadi (IOP Publishing, 2016)
A Q-switched ytterbium doped fiber laser (YDFL) with a ZnO saturable absorber (SA) is used to demonstrate the generation of pulses in the 1 micron region. The system has a Q-switching threshold of approximately 115.2 mW, and can generate pulses with a 3.0 µs full-width at half maximum as well as a peak-to-pedestal ratio of 53.0 dB. No spectral modulations are observed, indicating a highly stable system. The pulse output of the proposed system has repetition rates and pulse widths of approximately 50 kHz and 1.6 µs, as well as an average output power of 0.14 mW and a pulse energy of 2.8 nJ at its highest pump power of 196 mW. This is the first time, to the authors' knowledge, that a ZnO based SA has been used to generate pulses in the 1 micron region with a YDFL.